Europe and Central Asia Economic Update, Fall 2019 : Migration and Brain Drain - World Bank (Washington, DC: World Bank, 2019)
The share of immigrants in Western and Eastern Europe has increased rapidly over the past four decades. Today, one of every three immigrants in the world goes to Europe. Furthermore, although globally only one-third of migration takes place within regions, intraregional migration is especially high within Europe and Central Asia, with 80 percent of the region's emigrants choosing to move to other countries in the region. In high-income destination countries, migrants are often blamed for high unemployment and declining social services. There are also widespread concerns about brain drain in the migrant sending countries of Eastern Europe, the Western Balkans, and Central Asia. This update focuses on the design of policies on labor mobility and presents the trends, determinants, and impacts of low- and high-skilled labor.